FORMULASI SHEET MASK EKSTRAK ETANOL KULIT PISANG AMBON (Musa paradisiaca L.) SEBAGAI MOISTURIZING - Adek Chan; Afriadi Afriadi; Hanafis Sastra Winata; Suprianto Suprianto; Sahrita Sahrita (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2021)
Ambon banana peel contains flavonoid chemical compounds that can moisturize facial skin. Flavonoids are powerful antioxidants. A sheet mask formulation of Ambon banana peel extract that can be used more practically and is able to moisturize facial skin. This study aims to formulate a mask sheet preparation containing ethanol extract of Ambon banana peel as well as better skin maintenance for four weeks of treatment and measuring the moisture content of the skin. The research method used is an experimental method, namely the extract is obtained using the maceration method, then formulated into a sheet mask preparation, consisting of glycerin, butylene glycol, sodium polyacrylate, nipagin, PEG-40 Hydrogenated Castrol oil, aquadest, perfume, and banana peel ethanol extract. Ambon with concentrations of F1 (1%), F2 (3%), F3 (5%), F4 (7%), F5 (9%), respectively. As blank (F0) sheet mask preparation without the addition of extract. The preparation is evaluated including homogeneity test, pH test, stability test, irritation test, Moisture effectiveness test using Moisture Checker and preference test. The treatment is carried out for 4 weeks by applying the mask twice a week. Data obtained from the analysis using the SPSS program. The results showed that the ethanol extract of Ambon banana peel can be formulated in a homogeneous sheet mask preparation, does not change color and remains stable in 4 weeks of storage with a pH of 4.6 - 6.6. Conclusion The ethanol extract of Ambon banana peel can be formulated into sheet masks with concentrations of 1%, 3%, 5%, 7% and 9% with a positive control ratio.